Analisis Faktor yang Berhubungan dengan Self-Awareness Perawatan Kaki pada Pasien DM Tipe 2 - Kurnia Harli; Irfan Irfan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the factors that influence type 2 DM patients' self-awareness in independent foot care. This study used an analytic survey design with a cross-sectional study approach. The results showed that most of the respondents were in the age range of 45-54 years. Most of the respondents were female, as much as 64.6%, most of the respondents were educated, and as many as 52.1% worked. Most of the respondents have low incomes (66.7%). In conclusion, several main factors influence foot care behavior in DM patients, including education, occupation, and income, which significantly influence foot care behavior in DM patients. Keywords: DM type II, Foot Care, Self-awareness